Self-adhesive biomaterial and its application
By using self-adhesive biological materials in self-fixed hernia repair patches, combined with self-adhesive layers of decellularized substrate and crosslinked network structure, the problem of poor fixation effect of existing patches is solved, and efficient biological patch fixation and tissue repair are achieved.
Patent Information
- Application Number
- CN202410825462.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-06-25
AI Technical Summary
The existing self-fixed hernia repair patch has insufficient grip strength, the fixing effect is inaccurate, and it is difficult to deploy and apply the patch when laparoscopically operated.
A self-adhesive biological material is provided, including a self-adhesive layer of a decellularized substrate substrate and a crosslinked network structure, and a self-adhesive layer with high adhesive strength and stable bonding strength is formed by encapsulating the end-group modified polyethylene glycol into a decellularized matrix degrader scaffold.
Effective fixation of biological patches is achieved, the problems of edge curling, shrinking and dislocation of patches are overcome, the bonding strength and stability are improved, and tissue repair is promoted.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical materials, and in particular relates to a self-adhesive biomaterial and a preparation method thereof. Background Art
[0002] With the popularity of tension-free herniorrhaphy, the application of materials to repair abdominal wall defects has become one of the important means of abdominal wall surgery. During the operation, the methods of fixing repair materials such as patches are sutures, hernia fixators and medical glue. Among them, suture suturing is difficult and time-consuming in surgical operations, especially laparoscopic operations, and is not convenient for clinical application; hernia fixators are simple to operate, but there are sutures that damage blood vessels and nerves, and the price is relatively high; medical glue has the functions of embolization, hemostasis, sealing and bonding, but when used to fix patches, it still needs to be sprayed in advance, and the amount is not easy to control. Excessive use may cause the problem of long-term difficulty in degradation.
[0003] At present, the self-fixing patch is mainly made of synthetic materials with micro-hooks attached to one side. For example, CN106923930B discloses a patch based on a new weaving technology and shape and its weaving method, including a mesh layer woven from a line made of polypropylene material and a first degradable layer made of a degradable material, and the mesh layer is provided with an anchoring structure. CN207041596U discloses a degradable self-fixing hernia repair patch, including a mesh structure mixed with polypropylene monofilaments and degradable polylactic acid monofilaments, and arranged with self-fixing micro-hooks that can grasp the abdominal wall tissue to realize the patch. CN102772271B discloses a self-fixing tissue patch, including a polypropylene material mesh layer and a degradable material hook surface layer fixed on the lower surface of the mesh layer, and the hook surface layer has the function of positioning and preventing the patch from sliding. However, the design hook strength of the above self-fixing patch is insufficient, the fixing effect is not accurate, and under laparoscopy, the patch needs to be curled into the abdominal cavity, and because the hooks are hooked with each other, the patch after entering the abdominal cavity is difficult to unfold and cannot be used. Therefore, it is necessary to develop a self-fixing repair material that can solve the above problems. Summary of the invention
[0004] In order to solve the above problems, the first aspect of the present invention provides a self-adhesive biomaterial, including a base layer and a self-adhesive layer, the contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer, the base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.10mm-1.00mm.
[0005] In the present invention, the contact area S between the base layer and the self-adhesive layer of the self-adhesive biomaterial is not limited and can be adjusted according to actual needs. The base layer and the self-adhesive layer can be in 100% contact or in partial contact.
[0006] Preferably, the self-adhesive layer is a cross-linked network structure with a thickness of 0.10 mm-1.00 mm.
[0007] Further preferably, the self-adhesive layer is a cross-linked network structure with a thickness of 0.10 mm-0.80 mm.
[0008] More preferably, the self-adhesive layer is a cross-linked network structure with a thickness of 0.10 mm to 0.50 mm.
[0009] The decellularized substrate in the present invention is not particularly limited, and commercially available decellularized substrates can be used in the present invention. Examples include: biological hernia repair patch (National Medical Device Registration No. 20213130873) and dura mater repair patch (National Medical Device Registration No. 20223131768) of Zhuoruan Medical Technology (Suzhou) Co., Ltd.
[0010] As a preferred embodiment, the self-adhesive layer is obtained by encapsulating terminal-modified polyethylene glycol into a decellularized matrix degradation product scaffold.
[0011] As a preferred embodiment, the terminal group-modified polyethylene glycol is selected from one or more of anhydride-modified polyethylene glycol, aldehyde-modified polyethylene glycol, succinimide-modified polyethylene glycol, and maleimide-modified polyethylene glycol.
[0012] As a preferred embodiment, the terminal-modified polyethylene glycol is succinimide-modified polyethylene glycol.
[0013] More preferably, the succinimidyl-modified polyethylene glycol is one or more of two-arm-polyethylene glycol-succinimidyl ester, four-arm-polyethylene glycol-succinimidyl ester, and eight-arm-polyethylene glycol-succinimidyl ester.
[0014] More preferably, the succinimidyl-modified polyethylene glycol is four-arm-polyethylene glycol-succinimidyl ester or a mixture of four-arm-polyethylene glycol-succinimidyl ester and eight-arm-polyethylene glycol-succinimidyl ester.
[0015] Preferably, in the mixture of four-arm-polyethylene glycol-succinimidyl ester and eight-arm-polyethylene glycol-succinimidyl ester, the weight ratio of four-arm-polyethylene glycol-succinimidyl ester to eight-arm-polyethylene glycol-succinimidyl ester is (85-100):(10-35).
[0016] Preferably, the four-arm-polyethylene glycol-succinimidyl ester is four-arm-polyethylene glycol-succinimidyl succinate (4ARM-PEG-SS); and the eight-arm-polyethylene glycol-succinimidyl ester is eight-arm-polyethylene glycol-succinimidyl succinate (8ARM-PEG-SS).
[0017] The more modified groups there are on the terminal modified polyethylene glycol, the greater the bonding strength between the self-adhesive layer and the tissue will be when used. This has indeed been confirmed in the experiment. The bonding strength of the self-adhesive biomaterial obtained using 8ARM-PEG-SS is significantly higher than that of 4-arm PEG-SIS. However, it was found during the operation that 8ARM-PEG-SS will absorb moisture significantly during the weighing process, which will affect the stability of the product and increase the uncontrollability of use. Therefore, the present invention is not suitable for using 8ARM-PEG-SS, especially in the scenario of large-scale production. However, the inventor unexpectedly discovered in the experiment that mixing 4ARM-PEG-SS and 8ARM-PEG-SS in a weight ratio of (85-100): (10-35) can overcome the instability caused by the moisture absorption of 8ARM-PEG-SS, making the self-adhesive biomaterial have good stability while enhancing the bonding strength. It also unexpectedly improves the swelling of the self-adhesive layer of the self-adhesive biomaterial, thereby reducing its pressure on the tissue. The low swelling can ensure that the patch fits closely with the repaired tissue, promote the rapid vascularization of the patch to achieve tissue repair, and reduce the influence of the self-adhesive layer on the mechanical properties of the base layer (patch). In particular, the weight ratio of the end-group modified polyethylene glycol to the decellularized matrix degradation scaffold is further controlled (4-16): 5, and the above effect is particularly prominent. This may be because the addition of a specific amount of 8ARM-PEG-SS limits the movement and diffusion of molecules in the polymer network, which has a certain impact on the packaging process of the melt negative pressure filling method, thereby affecting the performance of the self-adhesive biomaterial.
[0018] As a preferred embodiment, the decellularized matrix degradation product scaffold is selected from one or more of decellularized matrix degradation products, branched amino acid polymers, thiol-ene monomer polymers, and amino dextran.
[0019] Preferably, the decellularized matrix degradation product scaffold is selected from at least one of a decellularized matrix degradation product, a branched amino acid polymer, and an amino-dextran.
[0020] Further preferably, the decellularized matrix degradation product scaffold is a decellularized matrix degradation product, or a mixture of a decellularized matrix degradation product and a branched amino acid polymer.
[0021] In the mixture of the decellularized matrix degradation product and the branched amino acid polymer, the weight ratio of the decellularized matrix degradation product to the branched amino acid polymer is (50-100): (5-25).
[0022] The preparation method of the decellularized matrix degradation product is as follows: 0.05-0.8mmol / mL protease aqueous solution is adjusted to an acidic pH, decellularized particles are added so that the weight proportion of the decellularized particles in the protease aqueous solution is 1-20wt%, filtered after standing, the filtrate is taken, and the filtrate is dialyzed to obtain the product.
[0023] The protease is not particularly limited, and may be trypsin, pepsin, or the like.
[0024] Preferably, the weight proportion of the decellularized particles in the aqueous solution of protease is 1-15 wt %.
[0025] Preferably, the weight proportion of the decellularized particles in the protease aqueous solution is 1-10 wt %.
[0026] The decellularized particles are prepared by physically grinding the decellularized matrix into powder.
[0027] The decellularized matrix is selected from at least one of small intestinal submucosa, porcine bladder decellularized matrix, peritoneum, pericardium, and dermis.
[0028] In the present invention, the small intestinal submucosa and porcine bladder decellularized matrix were purchased from Zhuoruan Medical Technology (Suzhou) Co., Ltd.
[0029] Preferably, the branched amino acid polymer is one of polylysine, polyarginine and polyornithine.
[0030] More preferably, the branched amino acid polymer is polylysine or polyarginine.
[0031] As a preferred embodiment, the decellularized matrix degradation product scaffold is a porous structure with a pore size of 0.1 μm-500 μm.
[0032] As a preferred embodiment, the weight ratio of the terminal-modified polyethylene glycol to the decellularized matrix degradation product scaffold is (4-25):5.
[0033] Preferably, the weight ratio of the terminal-modified polyethylene glycol to the decellularized matrix degradation product scaffold is (4-20):5.
[0034] More preferably, the weight ratio of the end-group modified polyethylene glycol to the decellularized matrix degradation product scaffold is (4-16):5.
[0035] As a preferred embodiment, the preparation method of the self-adhesive biomaterial is as follows:
[0036] S1. Spread the decellularized substrate into a mold to obtain a base layer;
[0037] S2. After the surface of the base layer is coated with the decellularized matrix degradation scaffold, it is freeze-dried;
[0038] S3. Encapsulate the end-group modified polyethylene glycol into the decellularized matrix degradation product scaffold, and demold the scaffold to obtain the product.
[0039] As a preferred embodiment, the encapsulation method is a negative pressure filling method or an infiltration method, and the negative pressure filling method is a melting negative pressure filling method or a room temperature negative pressure filling method.
[0040] Preferably, the packaging method is a negative pressure filling method, and the negative pressure filling method is a melting negative pressure filling method.
[0041] Step S3: encapsulating the terminal-modified polyethylene glycol into the decellularized matrix degradation material scaffold by a melt negative pressure filling method, and demolding to obtain the product.
[0042] Further preferably, the encapsulation method in step S3 is specifically to heat the base layer coated with the decellular matrix degradation product scaffold after freeze-drying in step S2 to 55-65°C, so that the decellular matrix degradation product scaffold is in a molten state at this time, add powdered end-group modified polyethylene glycol, evacuate, make the reaction atmosphere in a negative pressure state, and encapsulate the end-group modified polyethylene glycol into the porous structure of the decellular matrix degradation product scaffold, so that the end-group modified polyethylene glycol and the decellular matrix degradation product scaffold are in a mixed state, and after 5-30 minutes, stop evacuating, restore the reaction atmosphere to a normal pressure state, cool to room temperature, and demold to obtain.
[0043] In the encapsulation process of step S3, due to the structural characteristics of the end-group modified polyethylene glycol, if the encapsulation process is in a water environment, it will cause the structural transformation of the end-group modified polyethylene glycol, so this process should avoid water molecules from participating in the encapsulation. The inventor has devoted a lot of creative work to find that the use of the molten negative pressure filling method for encapsulation can not only successfully achieve the encapsulation of the end-group modified polyethylene glycol in an anhydrous environment, but also whether the decellularized matrix degradation scaffold is a decellularized matrix degradation product or a mixture of a decellularized matrix degradation product and a branched amino acid polymer, it can improve the cell compatibility of the self-adhesive layer in the adhesive biomaterial, and at the same time reduce the acidic environment of the decellularized matrix degradation product. The adverse effect of the gelation time and mechanical properties of the self-adhesive layer. The inventor speculates that the encapsulation process environment of the molten negative pressure filling method affects the flexibility of the molecular chain, reduces the change in steric hindrance, and further reacts on the degree of freedom of the molecular chain, affects the binding efficiency between molecules, and leads to the adjustment of the force.
[0044] A second aspect of the present invention provides an application of a self-adhesive biomaterial in the field of tissue repair.
[0045] Especially the application of self-adhesive biomaterials in the field of abdominal and pelvic floor repair and reconstruction.
[0046] When the self-adhesive biomaterial of the present invention is used for tissue repair, the specific method of use is: after the self-adhesive biomaterial obtained by the present invention is directly laid on the desired wound surface, 0.5-10mL PBS buffer solution is sprayed with a spray bottle, or with the help of tissue fluid on the tissue surface, the self-adhesive layer is firmly attached to the tissue.
[0047] Beneficial effects: The self-adhesive biomaterial obtained by the present invention has the effects of hemostasis, sealing and bonding. When the self-adhesive biomaterial is used, it is not necessary to spray the adhesive on the sprayer in advance. Instead, after the self-adhesive biomaterial is laid on the desired wound surface, a small amount of PBS buffer solution is directly sprayed with a spray bottle, or with the help of tissue fluid on the tissue surface. The dosage is easy to control, and it is completely degradable and does not cause safety problems. By adjusting the weight ratio of 4ARM-PEG-SS and 8ARM-PEG-SS, the instability caused by the moisture absorption phenomenon of 8ARM-PEG-SS can be overcome, so that the self-adhesive biomaterial has good stability, and the bonding strength is also enhanced, the swelling of the self-adhesive layer of the self-adhesive biomaterial is improved, and its pressure on the tissue is reduced. The low swelling can ensure that the patch fits closely with the repair tissue, promote the rapid vascularization of the patch to achieve tissue repair, and reduce the influence of the self-adhesive layer on the mechanical properties of the base layer (patch). Through the creative design of the encapsulation process in step S3, not only can the encapsulation of end-group-modified polyethylene glycol be successfully achieved in an anhydrous environment, but also the cell compatibility of the self-adhesive layer in the adhesive biomaterial can be improved regardless of whether the decellularized matrix degradation product scaffold is a decellularized matrix degradation product or a mixture of a decellularized matrix degradation product and a branched amino acid polymer, while also reducing the adverse effects of the acidic environment of the decellularized matrix degradation product on the gelation time and mechanical properties of the self-adhesive layer.
[0048] In the field of patch repair, rolled-up edges of patches placed in the abdominal cavity, loose patches that are not fully flattened, and patch displacement are high-risk factors for intestinal adhesion, erosion, and bulging. The self-adhesive biomaterial obtained by the present invention can effectively fix the biological patch, effectively overcome the above problems, and make the biological patch less likely to curl and shrink. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 Step S2 of the method for preparing the self-adhesive biomaterial prepared in Example 1. Front view of the decellularized matrix degradation product scaffold coated on the surface of the base layer, in which: 1-self-adhesive layer, 2-mold, 3-base layer;
[0050] Figure 2 Step S2 of the method for preparing the self-adhesive biomaterial prepared in Example 1: a top view of the decellularized matrix degradation product scaffold coated on the surface of the base layer;
[0051] Figure 3 This is a front view of the end-group modified polyethylene glycol in step S3 of the preparation method of the self-adhesive biomaterial prepared in Example 1 so as to be encapsulated into the porous structure of the decellularized matrix degradation material scaffold. In the figure, 4-end-group modified polyethylene glycol, 5-decellularized matrix degradation material scaffold;
[0052] Figure 4 This is a scanning electron microscope image of the self-adhesive biomaterial obtained in Example 1 before packaging in step S3;
[0053] Figure 5 This is a scanning electron microscope image of the self-adhesive biomaterial obtained in Example 1 after packaging in step S3;
[0054] Figure 6 This is a scanning electron microscope image of the self-adhesive biomaterial obtained in Comparative Example 2 before packaging in step S3;
[0055] Figure 7 This is a scanning electron microscope image of the self-adhesive biomaterial obtained in Comparative Example 2 after packaging in step S3;
[0056] Figure 8 This is a picture of the self-adhesive biomaterial obtained in Comparative Example 3 after being demoulded through steps S1-S3 and placed in a room temperature environment with a humidity of 10% for one week. DETAILED DESCRIPTION
[0057] The materials in the examples are all commercially available, among which the small intestinal submucosa and porcine bladder decellularized matrix were purchased from Zhuoruan Medical Technology (Suzhou) Co., Ltd.; polylysine was purchased from Maidehao Chemical, model ε-polylysine, 4arm-PEG-SS were purchased from Shanghai Chuangsai Technology Co., Ltd., and 8arm-PEG-SS were purchased from Huateng Pharmaceutical; pepsin was purchased from Ruiyang Biotechnology. Example 1
[0058] This example provides a self-adhesive biomaterial, including a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is an acellular substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.50 mm.
[0059] The decellularized substrate was purchased from Zhuoruan Medical Technology (Suzhou) Co., Ltd. and the product name is biological hernia repair patch.
[0060] The self-adhesive layer was obtained by encapsulating terminal-modified polyethylene glycol into the decellularized matrix degradation material scaffold.
[0061] The weight ratio of the terminal-modified polyethylene glycol to the decellularized matrix degradation product scaffold is 7:5.
[0062] The terminal modified polyethylene glycol is succinimidyl modified polyethylene glycol, the succinimidyl modified polyethylene glycol is four-arm-polyethylene glycol-succinimidyl ester, and the four-arm-polyethylene glycol-succinimidyl ester is four-arm-polyethylene glycol-succinimidyl succinate (4ARM-PEG-SS); the decellularized matrix degradation product scaffold is a decellularized matrix degradation product.
[0063] The preparation method of the decellularized matrix degradation product is as follows: the preparation method of the acidic enzymatic hydrolysate is as follows: a 0.32 mmol / mL pepsin aqueous solution is adjusted to an acidic pH, decellularized particles (prepared by physically grinding the small intestinal submucosal layer into powder) are added, so that the weight proportion of the decellularized particles in the protease aqueous solution is 10wt%, and the product is obtained after standing for full reaction and then filtered, the filtrate is taken, and the filtrate is dialyzed to obtain the product.
[0064] The decellularized matrix degradation material scaffold has a porous structure with a pore size of 0.1 μm-500 μm.
[0065] The preparation method of the self-adhesive biomaterial is as follows:
[0066] S1. Spread the decellularized substrate into a mold to obtain a base layer;
[0067] S2. The surface of the base layer is coated with a decellularized matrix degradation scaffold, such as Figure 1 , 50 μL of the decellularized matrix degradation scaffold was injected into each cylindrical mold hole and freeze-dried;
[0068] S3. Encapsulate the end-group modified polyethylene glycol into the decellularized matrix degradation product scaffold, and demold the scaffold to obtain the product.
[0069] The packaging method is a negative pressure filling method, and the negative pressure filling method is a melting negative pressure filling method.
[0070] Step S3: encapsulating the terminal-modified polyethylene glycol into the decellularized matrix degradation material scaffold by a melt negative pressure filling method, and demolding to obtain the product.
[0071] The encapsulation method in step S3 is specifically to heat the base layer coated with the decellularized matrix degradation product scaffold after freeze-drying in step S2 to 60° C., so that the decellularized matrix degradation product scaffold is in a molten state, add powdered terminal group-modified polyethylene glycol, evacuate the reaction atmosphere to a negative pressure state, and encapsulate the terminal group-modified polyethylene glycol into the porous structure of the decellularized matrix degradation product scaffold, so that the terminal group-modified polyethylene glycol and the decellularized matrix degradation product scaffold are in a mixed state, such as Figure 3 After 20 minutes, stop vacuuming, restore the reaction atmosphere to normal pressure, cool to room temperature, and then demould. Example 2
[0072] This example provides a self-adhesive biomaterial. The difference from Example 1 is that the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.48 mm.
[0073] The preparation method of the decellularized matrix degradation product is as follows: the preparation method of the acidic enzymatic hydrolyzate is as follows: a 0.32 mmol / mL pepsin aqueous solution is adjusted to an acidic pH, decellularized matrix particles (prepared by physically grinding the porcine bladder decellularized matrix into powder) are added, so that the weight proportion of the decellularized matrix particles in the protease aqueous solution is 10wt%, and the product is obtained after standing for full reaction and then filtered, the filtrate is taken, and the filtrate is dialyzed to obtain the product. Example 3
[0074] This example provides a self-adhesive biomaterial. Different from Example 1, the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.35 mm.
[0075] The decellularized matrix degradation material scaffold is a mixture of decellularized matrix degradation material and branched amino acid polymer.
[0076] In the mixture of the decellularized matrix degradation product and the branched amino acid polymer, the weight ratio of the decellularized matrix degradation product to the branched amino acid polymer is 79:15.
[0077] The branched amino acid polymer is polylysine. Example 4
[0078] This example provides a self-adhesive biomaterial. The difference from Example 1 is that the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.55 mm.
[0079] The self-adhesive layer was obtained by encapsulating terminal-modified polyethylene glycol into the decellularized matrix degradation material scaffold.
[0080] The weight ratio of the terminal-modified polyethylene glycol to the decellularized matrix degradation product scaffold is 6:5.
[0081] The succinimidyl modified polyethylene glycol is a mixture of four-arm-polyethylene glycol-succinimidyl ester and eight-arm-polyethylene glycol-succinimidyl ester; in the mixture of four-arm-polyethylene glycol-succinimidyl ester and eight-arm-polyethylene glycol-succinimidyl ester, the weight ratio of four-arm-polyethylene glycol-succinimidyl ester to eight-arm-polyethylene glycol-succinimidyl ester is 94:18; four-arm-polyethylene glycol-succinimidyl ester is four-arm-polyethylene glycol-succinimidyl succinate (4ARM-PEG-SS); eight-arm-polyethylene glycol-succinimidyl ester is eight-arm-polyethylene glycol-succinimidyl succinate (8ARM-PEG-SS).
[0082] Comparative Example 1
[0083] This example provides a self-adhesive biomaterial. The difference from Example 1 is that the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.46 mm.
[0084] The self-adhesive layer was obtained by encapsulating terminal-modified polyethylene glycol into the decellularized matrix degradation material scaffold.
[0085] The weight ratio of the terminal-modified polyethylene glycol to the decellularized matrix degradation product scaffold is 8:5.
[0086] The succinimidyl-modified polyethylene glycol is eight-arm-polyethylene glycol-succinimidyl ester, and the eight-arm-polyethylene glycol-succinimidyl ester is eight-arm-polyethylene glycol-succinimidyl succinate (8ARM-PEG-SS).
[0087] Comparative Example 2
[0088] This example provides a self-adhesive biomaterial. Different from Example 1, the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.26 mm.
[0089] The self-adhesive layer was obtained by encapsulating terminal-modified polyethylene glycol into the decellularized matrix degradation material scaffold.
[0090] The weight ratio of the terminal-modified polyethylene glycol to the decellularized matrix degradation product scaffold is 2:5.
[0091] Comparative Example 3
[0092] This example provides a self-adhesive biomaterial. Different from Example 4, the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.52 mm.
[0093] The self-adhesive layer was obtained by encapsulating terminal-modified polyethylene glycol into the decellularized matrix degradation material scaffold.
[0094] The weight ratio of the terminal-modified polyethylene glycol to the decellularized matrix degradation product scaffold is 2:5.
[0095] Comparative Example 4
[0096] This example provides a self-adhesive biomaterial. Different from Example 1, the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.58 mm.
[0097] In the method for preparing the self-adhesive biomaterial, in step S3, 70 μL of a 10 wt % aqueous solution of end-group-modified polyethylene glycol is poured onto the decellularized matrix degradation product scaffold of step S2, and the scaffold is demoulded after freeze-drying to obtain the self-adhesive biomaterial.
[0098] Comparative Example 5
[0099] This example provides a self-adhesive biomaterial. Different from Example 1, the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.43 mm.
[0100] In the method for preparing the self-adhesive biomaterial, in step S3, 1 mg of terminal-modified polyethylene glycol is placed on the decellularized matrix degradation product support of step S2, and the support is placed in a vacuum drying oven. After the negative pressure is drawn, the negative pressure environment is maintained for 15 minutes, and then the self-adhesive biomaterial is demolded.
[0101] Comparative Example 6
[0102] This example provides a self-adhesive biomaterial. The difference from Example 1 is that the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.46 mm.
[0103] The preparation method of the self-adhesive biomaterial is as follows: S1. The decellularized substrate is spread flat in a mold to obtain a base layer; S2. A 10wt% aqueous solution of end-group-modified polyethylene glycol and a decellularized matrix degradation product scaffold are mixed in a weight ratio of 7:5, coated on the base layer, and freeze-dried so that the thickness of the self-adhesive layer after freeze-drying is 0.46mm.
[0104] Comparative Example 7
[0105] This example provides a self-adhesive biomaterial. Different from Example 4, the self-adhesive biomaterial includes a base layer and a self-adhesive layer. The contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer. The base layer is a decellularized substrate; the self-adhesive layer is a cross-linked network structure with a thickness of 0.48 mm.
[0106] The self-adhesive layer was obtained by encapsulating terminal-modified polyethylene glycol into the decellularized matrix degradation material scaffold.
[0107] The succinimide-modified polyethylene glycol is a mixture of four-arm-polyethylene glycol-succinimidyl ester and eight-arm-polyethylene glycol-succinimidyl ester; in the mixture of four-arm-polyethylene glycol-succinimidyl ester and eight-arm-polyethylene glycol-succinimidyl ester, the weight ratio of four-arm-polyethylene glycol-succinimidyl ester to eight-arm-polyethylene glycol-succinimidyl ester is 64:36.
[0108] Results Test
[0109] 1. Scanning electron microscopy characterization: The self-adhesive layer of the self-adhesive biomaterial obtained in Example 1 and Comparative Example 2 was characterized by scanning electron microscopy before and after the encapsulation in step S3. Figure 4-7 , you can see, Figure 4 The porous structure shows that the decellularized matrix degradation scaffold has a porous structure before encapsulation. Figure 5 It can be seen that the end-group modified polyethylene glycol is encapsulated and filled into the decellularized matrix degradation scaffold, and the two are evenly mixed; Figure 6 and Figure 7 It can be clearly seen that the encapsulation and filling effect of the self-adhesive layer of the self-adhesive biomaterial in Comparative Example 2 is poor.
[0110] 2. Adhesion performance: Pigskin with a structure similar to human tissue was selected to perform lap-shear adhesion strength tests on the self-adhesive biomaterials of Examples 1-4 and Comparative Examples 1-6, respectively. The bonding area was 15 cm*10 cm. The self-adhesive biomaterial obtained by the present invention was directly laid on the pigskin, and 1 mL of PBS buffer solution was sprayed with a spray bottle. The gelation time of the self-adhesive layer of the self-adhesive biomaterial was measured by the inversion method. After gelation, referring to YY / T0729.1-2009, the calculation formula for testing the adhesion strength was as follows:
[0111]
[0112] The test results of gelation time and bonding strength are shown in Table 1. Another batch of new samples were bonded to pig skin according to the above method. After bonding, the samples were placed in a room temperature environment with a humidity of 80% for 1 week to observe whether the base layer of the self-adhesive biomaterial curled or shrunk.
[0113] Adhesion reaction mechanism: The terminal-modified polyethylene glycol in the self-adhesive layer of the self-adhesive biomaterial reacts with the amino group on the surface of the base layer to form interfacial adhesion force, the terminal-modified polyethylene glycol in the self-adhesive layer reacts with the amino group of the decellularized matrix degradation product scaffold to form cohesive force, and the terminal-modified polyethylene glycol in the self-adhesive layer reacts with the amino group on the surface of the pig skin tissue to form adhesion force on the tissue interface. The three forces work together to fix the self-adhesive biomaterial to the tissue.
[0114] Table 1
[0115]
[0116] In actual operation, too short a gelling time will shorten the operation window and increase the difficulty of the operation. In addition, too short a gelling time will also reduce the mechanical strength of the self-adhesive layer.
[0117] Figure 8This is a picture of the self-adhesive biomaterial obtained in comparative example 3 after demoulding in steps S1-S3 and placed in a room temperature environment with a humidity of 80% for one week. It can be seen from the picture that the base layer is obviously wrinkled.
[0118] 3. Swelling property: Select pig skin (length * width is 25 mm * 10 mm) with similar structure to human tissue and conduct lap-shear bonding strength test with self-adhesive biomaterials of Examples 1-4 and Comparative Examples 1-6 respectively. The bonding area is 25 mm * 10 mm. The self-adhesive biomaterial obtained by the present invention is directly laid on the pig skin, and 1 mL of PBS buffer solution is sprayed with a spray bottle. After curing for half an hour, the initial mass of the sample is measured and recorded as m0. The sample is immersed in physiological saline at 37°C and taken out after 4 hours. The excess water on the surface is absorbed with filter paper and then the mass is quickly weighed and recorded as m. The calculation formula is as follows:
[0119]
[0120] The results are shown in Table 2.
[0121] Table 2
[0122]
[0123] 4. Degradation performance: Select pig skin (length * width is 25 mm * 10 mm) with a structure similar to human tissue and conduct lap-shear bonding strength test with the self-adhesive biomaterials of Examples 1-4 and Comparative Examples 1-6, respectively. The bonding area is 25 mm * 10 mm. The self-adhesive biomaterial obtained by the present invention is directly laid on the pig skin, and 1 mL of PBS buffer solution is sprayed with a spray bottle. After curing for half an hour, the initial mass of the sample is measured and recorded as m1. The sample is immersed in physiological saline at 37°C, and taken out after 1 day, 3 days, 5 days, 7 days, 14 days, and 21 days, rinsed with deionized water, and dried to constant weight. The mass is recorded as mn. The calculation formula is as follows:
[0124]
[0125] The results show that the in vitro degradation rates of Examples 1-4 and Comparative Example 1 on the 14th day all reached more than 50%, among which the in vitro degradation rate of Comparative Example 1 on the 5th day reached 50%. In practice, the faster the degradation rate, the better. If the degradation rate is too fast, it is not conducive to the recovery of the wound after implantation of the wound tissue; the in vitro degradation rates of Comparative Examples 2-6 on the 14th day did not reach 50%. When taken out after the 21st day, the in vitro degradation rates of Comparative Examples 2-6 still did not reach 70%, while the in vitro degradation rates of Examples 1-4 and Comparative Example 1 all reached more than 85%. The above results show that the self-adhesive biomaterials of Examples 1-4 have good degradation performance, the degradation rate of the self-adhesive biomaterial of Comparative Example 1 is too fast, and such degradation performance is not conducive to practical application, and the in vitro degradation rate of Comparative Examples 2-6 is too slow, and such degradation performance is not conducive to practical application.
[0126] 5. Sealing test: Referring to ASTM F2392-04, the self-adhesive biomaterials of Examples 1-4 and Comparative Examples 1-6 were adhered to pig stomach tissue and the bursting strength was measured after curing at room temperature for 10 min. A peristaltic pump was used to pass physiological saline into one end of the device, and a pressure gauge was connected to the other end to measure the maximum water pressure that the sample could withstand. The results are shown in Table 4.
[0127] Table 4
[0128]
[0129] 6. Cytocompatibility: After sterilization, the self-adhesive biomaterials of Example 1, Example 4 and Comparative Examples 1-6 were immersed in high-glucose DMEM supplemented with 1% (v / v) double antibody, with a solid-liquid ratio of 1 g: 10 ml, and incubated in a shaker at 37°C for 1 day, 3 days and 7 days respectively. The supernatant after incubation was taken, 10% (v / v) serum (FBS) was added, and diluted to 3 concentrations (1×, 10×, 100×) with cell culture medium (1% double antibody, 10% FBS, 89% DMEM) to obtain adhesive extracts.
[0130] L929 cells were seeded in 24-well culture plates with a medium volume of 400 μL / well and a cell seeding density of 1×10 4 / well, and cultured in a cell culture incubator at a constant temperature for 24 hours. Replace the culture medium in each well of the 24-well plate with the above-mentioned adhesive extract diluted at different times, and continue to culture in the cell culture incubator for 24 hours. At the same time, set up a culture medium without extract as an experimental control group. The number of stock cells was tested with the help of the MTT kit, and the absorbance value (OD value) of each well was measured at 490 nm with an enzyme marker. TCP (tissue culture plate) was used as a blank control. The formula for calculating the cell proliferation rate is as follows:
[0131]
[0132] The results showed that the cell proliferation rates were as follows from largest to smallest: Example 1 > Example 4 > Comparative Example 2 > Comparative Example 3 > Comparative Example 1 > Comparative Example 5 > Comparative Example 4 > Comparative Example 6.
[0133] 7. Stability study: For Examples 1-4 and Comparative Example 1 and Comparative Example 7, 20 parallel experiments were conducted respectively to test the bonding strength, swelling and sealing properties of the samples, and the relative standard deviations (RSD) of the bonding strength, swelling and sealing properties of the 20 parallel experiments were calculated. The results are shown in Table 5:
[0134] Table 5
[0135]
Claims
1. A self-adhesive biomaterial, comprising a base layer and a self-adhesive layer, wherein the contact area between the base layer and the self-adhesive layer is S, 0<S≤the area of the base layer, characterized in that: The base layer is an acellular base material; the self-adhesive layer is a cross-linked network structure with a thickness of 0.10 mm to 1.00 mm; The self-adhesive layer is obtained by encapsulating terminal-modified polyethylene glycol into the decellularized matrix degradation material scaffold; The decellularized matrix degradation material scaffold is a decellularized matrix degradation material, or a mixture of a decellularized matrix degradation material and a branched amino acid polymer. The weight ratio of the terminal modified polyethylene glycol to the decellularized matrix degradation material scaffold is (4-25):
5. The packaging method is a negative pressure filling method, and the negative pressure filling method is a melt negative pressure filling method.
2. The self-adhesive biomaterial according to claim 1, characterized in that: The terminal group-modified polyethylene glycol is succinimide-modified polyethylene glycol.
3. The self-adhesive biomaterial according to claim 1, characterized in that: The terminal group-modified polyethylene glycol is selected from one or more of anhydride-modified polyethylene glycol, aldehyde-modified polyethylene glycol, succinimide-modified polyethylene glycol, and maleimide-modified polyethylene glycol.
4. The self-adhesive biomaterial according to claim 1, characterized in that: The decellularized matrix degradation product scaffold is a porous structure with a pore size of 0.1 μm-500 μm.
5. The self-adhesive biomaterial according to claim 1, characterized in that: The preparation method of the self-adhesive biomaterial is as follows: S1. Spread the decellularized substrate into a mold to obtain a base layer; S2. After the surface of the base layer is coated with the decellularized matrix degradation scaffold, it is freeze-dried; S3. Encapsulate the end-group modified polyethylene glycol into the decellularized matrix degradation product scaffold, and demold the scaffold to obtain the product.
Citation Information
Patent Citations
Self-fixing tissue patch
CN102772271B
Patch based on new weaving technology and shape and its weaving method
CN106923930B
Degradable is from fixed hernia repair patch
CN207041596U
PEG (polyethylene glycol) two-component self-adhesive absorbable biological patch as well as preparation method and application thereof
CN115814163A
Medical gel dressing as well as preparation method and application thereof
CN116983466A